Training citizen competences for a global world - Sánchez Tarrillo, Segundo Juan (2021)
Abstract Today's society is going through a series of transformations that include uncertainties, accelerated changes that, in a certain way, also generated responses and consequences in a divided, fragmented, intolerant and not very empathetic society; for this reason, more than ever, responsible citizens are needed to improve society. This article is the report of a research whose purpose was to develop a systematic analysis of the formation and development of civic competencies to respond to a globalized world. The research was carried out by means of a systematic review with a meta-analytical nature of various publications, for which information providers and multiple scientific databases indexed in: ProQuest, Ebsco, SciELO, Scopus, Concytec, Dialnet, among others, were used. In the same way, using Boolean terms and operators, a meta-search was carried out in Google Scholar of reports and repositories published by international and national organizations and institutions such as: UNESCO, CEPAL, UNICEF, INEI, CADE-IPAE. The articles and reports analyzed describe global problems, offer various didactic and pedagogical strategies to improve coexistence and develop citizens' civic skills. Likewise, the inclusion criteria of reliable sources from the last five years were considered, as well as the exclusion of some articles for not being subject to validity and reliability. Finally, it is concluded that most researchers have published studies in order to develop a culture of peace. Given this, the reports that stand out are quantitative, qualitative and mixed, many of which seek to strengthen citizenship competencies at different levels: basic and superior, highlighting Colombia as the country with the greatest impact in publications on the formation of citizenship competencies. Keywords: basic training, life skills, citizenship skills, global citizenship and global education.